The effect of composition on CO2 Freeze-Out and Critical Locus of Binary CO2âCH4 Mixture - Babar, M. (Springer Science and Business Media Deutschland GmbH, 2020)
Cryogenic CO2 capture technology is one of the emerging technologies used for natural gas purification. Thermodynamic phase study of the natural gas has a significant effect on the cryogenic CO2 removal from natural gas. The present work describes the impact of composition on CO2 freeze-out and critical locus of the binary CO2âCH4 mixtures with different CO2 content. Critical locus and CO2 freeze-out were modelled for nine binary CO2âCH4 mixtures and were correlated with the composition of the binary mixtures. Aspen HYSYS version 8.0 with the Peng Robinson equation of state and Eureka modelling tool were used in the present research work. It was found that the predicted models can precisely calculate the CO2 freeze-out point and the critical locus of the mixtures. By comparing the calculated data with the reported experimental data, an excellent agreement was found. R-squared value for the models was 0.99, which shows the reliability of the models. The effect of composition on three-phase loci of the binary and multicomponent mixtures of CO2 with light H.C is recommended for future research. Â© Springer Nature Singapore Pte Ltd 2020.